2021
DOI: 10.1088/1741-2552/abcefe
|View full text |Cite
|
Sign up to set email alerts
|

Decoding working memory task condition using magnetoencephalography source level long-range phase coupling patterns

Abstract: Objective. The objective of the study is to identify phase coupling patterns that are shared across subjects via a machine learning approach that utilises source space magnetoencephalography (MEG) phase coupling data from a working memory (WM) task. Indeed, phase coupling of neural oscillations is putatively a key factor for communication between distant brain areas and is therefore crucial in performing cognitive tasks, including WM. Previous studies investigating phase coupling during cognitive tasks have of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…The latest release supports different signal characteristics as features, such as the power envelope or the instantaneous phase of the signal. Recent studies [90] implement different feature engineering techniques, concatenating data from different frequency bands, to improve the classification result. Currently, MVPAlab does not implement these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The latest release supports different signal characteristics as features, such as the power envelope or the instantaneous phase of the signal. Recent studies [90] implement different feature engineering techniques, concatenating data from different frequency bands, to improve the classification result. Currently, MVPAlab does not implement these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…During and following the early stimulus encoding phase, several WM neurophysiological studies report an eventrelated desynchronisation (ERD) of the occipital alpha activity 11,[38][39][40] . This effect resembles the significant deactivation of state 2 between 200-500 ms PST.…”
Section: State 2 -Local Processing and Memory Storagementioning
confidence: 99%
“…The broadband activity of this state reflects the diversified frequency bands (theta, alpha, beta, and gamma) associated with maintenance, recall, matching, and motor plan 32,55,56 , and the intertwined development of these processes during an n-back task. A developing research line identifies cross-frequency coupling as the underlying mechanism for WM subprocesses, explaining the broadband activity reported by traditional works 40,[56][57][58] . In this context, we would suggest that the broadband spectral profile of state 5 results from cross-frequency interactions.…”
Section: State 5 -An M300 Statementioning
confidence: 99%
“…Indeed, it has been demonstrated that MVPA can be successfully used to discriminate patterns of brain activation in perceptual and cognitive tasks (Cichy et al 2014 ; Guidotti et al 2020 ; Kragel and LaBar 2016 ; Tosoni et al 2016 ). The same approach has been used by exploiting functional connectivity patterns to decode discrete functions such as working memory (Syrjälä et al 2021 ) or continuous variables such as brain maturity or age (Dosenbach et al 2010 ; Liem et al 2017 ). Moreover, MVPA has been applied in mindfulness studies to predict age using voxel-based morphometry (Luders et al 2016 ) and to classify patterns of functional connectivity before and after a body-mind training course (Tang et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%